A Unified Instability Region for the Extended Taylor-Goldstein Problem of Hydrodynamic Stability (Advances in Applied Mathematics and Mechanics, 2021)
We consider inviscid, incompressible shear flows with variable density andvariable cross section. For this problem, we derived a new estimate for the growth rateof an unstable mode and a parabolic instability region which intersects semiellipseinstability region under some condition.